Nutritional Modulation of Insulin Resistance - Martin O. Weickert (Scientifica)
Insulin resistance has been proposed as the strongest single predictor for the development of Type 2 Diabetes (T2DM). Chronic oversupply of energy from food, together with inadequate physical activity, have been recognized as the most relevant factors leading to overweight, abdominal adiposity, insulin resistance, and finally T2DM. Conversely, energy reduced diets almost invariably to facilitate weight loss and reduce abdominal fat mass and insulin resistance. However, sustained weight loss is generally difficult to achieve, and distinct metabolic characteristics in patients with T2DM further compromise success. Therefore, investigating the effects of modulating the macronutrient composition of isoenergetic diets is an interesting concept that may lead to additional important insights. Metabolic effects of various different dietary concepts and strategies have been claimed, but results from randomized controlled studies and particularly from longer-term-controlled interventions in humans are often lacking. However, some of these concepts are supported by recent research, at least in animal models and short-term studies in humans. This paper provides an update of the current literature regarding the role of nutrition in the modulation of insulin resistance, which includes the discussion of weight-loss-independent metabolic effects of commonly used dietary concepts.